An Analytical Study of Qur'anic Tafsir: Interpretation of Qur'anic Verses on Moral Education - Alfani, Ilzam Hubby Dzikrillah; Addzaky, Khoirul Umam; Mukhsin, Mukhsin; Malintang, Jimmy; Prabowo, Ari Yudhanto (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
This study aims to explore the values of moral education in the Qur'an. Considering the phenomenon today, many people are behaving who do not reflect good morals. This research uses a qualitative approach by relying on literature studies. The collected literature data were analyzed descriptively. The research found that in the Qur'an, there are verses that explain the concept and procedures of ethics/morals in everyday life. For example, Q.S. At-Taubah [9]: 119, which teaches to behave honestly. Q.S. Al-Baqarah [2]: 195) and Q.S. Al-A'raf [7]: 199 which teaches to be kind and compassionate. Q.S. Al-Baqarah [2]: 153 teaches to be patient. Q.S. Al-Ma'un [107]: 1-7 teaches to care about the environment. When referring to Q.S. Luqman [31]: 12-19, moral formation can be done early in the form of education from parents for their children. Among them are providing children's needs according to their portions, learning quietly and playing so that children grow, providing a conducive and positive environment, and integrated and istiqamah learning.